POLITICAL ECONOMY OF CATTLE COLONY: BETWEEN HERDERS-FARMERS CONFLICTS AND SUSTAINABLE DEVELOPMENT IN NIGERIA - Abada, Ifeanyichukwu Michael; Okafor, Nneka Ifeoma; Ofobuike, Chibueze Lawrence (PEOPLE: International Journal of Social Sciences, 2018)
In sub-Sahara African countries, agriculture has remained the mainstay of the economies. It has contributed to about 86.03% of the nations’ Gross Domestic Products (GDP). Nigeria being like every other nation state in Africa has been encouraged in the area of agriculture which stands tall to provide sustainability to the teeming population. In the recent time, the perceived serial conflicts between the Fulani herders and the indigenous farmers across the country has brought in fear of depletion of agricultural production, systemic disequilibrium and loss of lives and property. However, it is against this backdrop that the paper sets to appreciate the effects of herders-farmers conflicts on food production, sustainable national development and the political economy behind establishing cattle colonies across the country. Methodologically, the study appropriated qualitative method while generating its data and analyzed in content. The theoretical frame work of analysis is adequately anchored on the theory of eco-violence as propounded by Thomas Homer-Dixon (1988; 1999); and Gledistch, (2002). The findings of the study has adequately revealed that the serial conflicts between herders and the farmers had gravely undermined the contribution of agricultural sector, depleted internally generated revenue and loss of man power that would have sustained national development in Nigeria. The study strongly recommends among other; the voluntary giving out portion(s) of land by private individuals or purchase of land by the herders for their private businesses.